2017
DOI: 10.1007/s00192-017-3398-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for obstetric anal sphincter injuries (OASI) at a tertiary centre in south India

Abstract: Risk factors are similar to those in other population groups; however, primiparity appears to be associated with lesser risk and forceps delivery with greater risk of sphincter trauma than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
2
12
0
2
Order By: Relevance
“…Our study found prime gravidas at an increased risk for OASIS. Indeed, parity is a well-known risk factor for thirdand fourth-degree perineal tears [19,[28][29][30]. e most biologically plausible mechanism is the limited elasticity of the perineum among nulliparous and prime gravida women compared to multigravidas [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found prime gravidas at an increased risk for OASIS. Indeed, parity is a well-known risk factor for thirdand fourth-degree perineal tears [19,[28][29][30]. e most biologically plausible mechanism is the limited elasticity of the perineum among nulliparous and prime gravida women compared to multigravidas [31].…”
Section: Discussionmentioning
confidence: 99%
“…12 For the purpose of comparison, Marschalek et al, 2 in a national population-based study including only term single cephalic deliveries, reported a 2.6% incidence of OASIs. Similarly, a lower incidence, of 2.1%, was recently reported in an Indian tertiary healthcare center when the data was adjusted for birth weight > 500 g. 3 However, previous studies have reported higher rates of severe perineal tears in the group including term births only, ranging from 4.5 to 5.9%. 13,14 In the multivariate analysis, supine positions were associated with 53% of reduction in the rate of OASIs, whereas induced labor, analgesia, oxytocin use in the second stage of labor, and episiotomy did not have a significant effect.…”
Section: Discussionmentioning
confidence: 54%
“…The best maternal position adopted during the pelvic phase to avoid perineal damage is an issue that is still controversial, depending on a set of multifactorial predictors and specific subgroups of analysis. [1][2][3] High rates of obstetric anal sphincter injuries (OASIs) among women giving birth in the lithotomy position were reported in a population-based study 1 in Sweden on term non-instrumental births without episiotomy. However, another population-based research 2 in Austria, including primiparous term births, did not prove any effect of the birth positions on OASIs.…”
Section: Introductionmentioning
confidence: 99%
“…Hehir et al [4] in a retrospective study found that episiotomy was a protective factor in cases of shoulder dystocia (p = 0.006). Likewise, Gundabattula and Surampudi [16] demonstrated an association between dystocia and OAST (OR = 7.81, 95% CI = 4.30 -14.18; p = 0.000).…”
Section: Discussionmentioning
confidence: 87%
“…Conversely, some studies have observed mediolateral episiotomy as a protective factor for OAST. Zafran and Salim [15], in a retrospective study comparing selective and routine use of episiotomy, found that the incidence of OAST was significantly higher with selective use (OR = 2.23, 95% CI = 1.16 -4.29, p = 0.02) Gundabattula and Surampudi [16], in a retrospective study, evaluated the occurrence of OAST and identified episiotomy as a protective factor (OR = 0.57, 95% CI = 0.40 -0.83, p = 0.003) and Verghese et al [17], in a systematic review comparing OAST rates, found that episiotomy was a protective factor (RR = 0.67, 95% CI = 0.49 -0.92). In this review, all the studies evaluated were non-randomized, population-based or retrospective.…”
Section: Discussionmentioning
confidence: 99%